Individual Blade Pitch Control of Floating Offshore Wind Turbines for Load Mitigation and Power Regulation - Fitzgerald, Breiffni; Basu, Biswajit (My University, 2021)
This paper proposes a new strategy for individual blade pitch control to regulate power production while simultaneously alleviating structural loads on spar-type floating offshore wind turbines. Individual blade pitch control types of algorithms for offshore wind turbines are sparse in the literature though there are expected benefits from experience on such types of controllers for onshore wind turbines. Wind turbine blade pitch actuators are primarily used to maintain rated power production at above-rated wind speeds and therefore, control algorithms are usually developed only to regulate power production. The scope of reducing structural loads using individual pitch control has been proved to be very promising over the last decade and numerous individual pitch control algorithms have been proposed by researchers. However, reduction in structural loads often results in a degradation in power production and regulation. Furthermore, improving power regulation often has a detrimental effect on the floating platform motion. In this paper, a new control strategy is proposed to achieve the two competing objectives. The proposed controller combines a low authority Linear Quadratic (LQ) controller with an integral action to reduce the 1P (once per revolution) aerodynamic loads while regulating power production using the same pitch actuators that are traditionally used only to optimize power production. The proposed controller is compared against the baseline controller used by state-of-the-art wind turbine simulator FAST using a high fidelity aeroelastic offshore wind turbine model. Numerical results show that the proposed controller offers improved performance in optimizing power production and reducing wind turbine and platform loads compared to the baseline controller over an envelope of windwave loading environment.
PUBLISHED
Keywords: Floating offshore wind turbines; Individual blade pitch control; Regulate production; Alleviate aerodynamic loads; Smart & Sustainable Planet; ACTIVE CONTROL; CONTROL; CONTROL SYSTEMS; Control Engineering; Control Systems (Mechanical Engineering); Control Theory; Wind Energy and Wind Turbines; Wind Energy, General; Wind power; Wind, Wind Energy Engineering